Understanding the Dimensions of Caregiver-Perceived Seasonal Malaria Chemoprevention Delivery Quality in Nigeria: A Structural Equation Modeling Analysis of Door-to-Door Seasonal Malaria Chemoprevention - Tingkai Zhang; Sikai Huang; Taiwo Ibinaiye; Olusola Oresanya; Kevin Baker; Sol Richardson (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Seasonal malaria chemoprevention (SMC) with sulfadoxine–pyrimethamine and amodiaquine (AQ) has been implemented in Africa since 2012 to prevent malaria among children ages 3 to 59 months old. As SMC expands to new regions, concerns are emerging about sustainability and quality of implementation. Successful SMC delivery depends on not only effective drug administration but also caregiver engagement, adherence to at-home AQ administration, retention of Child Record Cards, and overall malaria prevention practices. Although caregivers’ perceptions of delivery quality as well as knowledge and trust of SMC may play critical roles in shaping these behaviors, these associations remain underexplored. We conducted secondary analyses of SMC delivery quality and its associations with key SMC outcomes using two cross-sectional end-of-round SMC coverage surveys in 11 Nigerian states in 2021 and 2022 ( N = 22,122). Exploratory factor analysis identified a single latent factor representing perceived SMC delivery quality based on six items reflecting distributor behavior and quality of communication. Logistic regression models revealed significant positive associations between higher index scores and days 2 and 3 AQ adherence as well as Child Record Card retention. Higher delivery quality was associated with reduced caregiver refusal of SMC. Structural equation modeling showed that perceived SMC delivery quality had significant direct effects on all three outcomes, with indirect effects significant only for days 2 and 3 AQ adherence. Findings highlight that improving and monitoring caregiver-perceived SMC delivery quality is essential to sustaining SMC effectiveness and suggest the need for strengthened distributor training and community engagement.